Executive Work Experience and Company Investment Efficiency - Septiani, Nabilla; Suryani, Ani Wilujeng (Journal of Accounting Research, Organization and Economics, 2024)
Objective - The growth as well as the longevity of a firm are determined by the investment in fixed assets. This strategy requires a competent manager to ensure the optimal utilization of investment options. According to the upper echelon theory, performance can be influenced by experience. Managerial experience and competence can result in effective resource allocation, reduce resource wastage, increase profitability, and accelerate company growth. Our study aims to investigate how the job experience in accounting and/or finance of the Chief Executive Officer (CEO) and Chief Financial Officer (CFO) affects investment efficiency.Design/Methodology - The study was conducted on 171 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. We used generalized least square regression to test the hypotheses.Results - The study found that CEOs with work experience in accounting and/or finance tend to reduce inefficient investments. However, this relationship does not hold true for CFOs.Research limitations/implications - The study indicates that the CEO's accounting and financial expertise is vital in facilitating effective investment choices. Therefore, companies should consider work experience, particularly in the field of accounting and/or finance, to enhance managerial performance in achieving investment efficiency, consequently leading to an increase in profitability and growth for the company.Novelty/Originality - Prior research examined the influence of the work experience of CEOs and CFOs as auditors on the efficiency of a company's investments. This study incorporates the work experience of CEOs and CFOs in accounting and/or other financial domains.